Reconstruction of the bubble nucleating potential - Amendola, Luca (Physical review. D, Particles, fields, gravitation, and cosmology, 1996)
We calculate analytically the bubble nucleation rate in a model of first-order inflation which is able to produce the large-scale structure. The computation includes the first-order departure from the thin-wall limit, the explicit derivation of the preexponential factor, and the gravitational correction. The resulting bubble spectrum then is compared with constraints from the large-scale structure and the microwave background. We show that there are models which pass all the constraints and produce bubblelike perturbations of interesting size. Furthermore, we show that it is in principle, possible to reconstruct completely the inflationary two-field potential from observations.
Gesehen am 20.11.2017